PENERAPAN PRINSIP ACTIO PAULIANA DALAM KEPAILITAN DAN PERLINDUNGAN HUKUMNYA TERHADAP PEMBELI YANG BERITIKAD BAIK - Anita Kamilah (Universitas Suryakancana, 2021)
Covid-19 pandemic situation has had a major impact on the sustainability of the community's businesses, thus hampering them in fulfilling their responsibilities in paying their debt obligations. Actio Pauliana as an instrument in the bankruptcy law on the one hand protects the interests of creditors, but on the other hand it is necessary to pay attention to the legal protection of buyers with good intentions. This research was conducted to examine: (1) Legal protection for creditors due to:Â transfer of the object of bankruptcy; and (2) the legal consequences of canceling the sale and purchase of objects bankruptcy and its protection against buyers in good faith. The approach method used is through a normative juridical approach, descriptive analysis research specifications, which are supported by types and sources of data derived from secondary data, especially primary legal materials, secondary legal materials, and tertiary legal materials, then qualitative data analysis is carried out. The results of the study: (1) the Bankruptcy Act and the provisions of the Civil Code as general provisions provide protection to creditors due to the transfer of the object of bankruptcy through the instrument Actio Pauliana to cancel the debtor's actions are detrimental to the creditor; and (2) Good faith buyers get protection to get his right to get a guarantee of the safe and secure goods he bought, and failure to fulfill it gives the buyer the right to claim compensation. Keywords: Bankruptcy, Actio Pauliana, Good faith, Buyer Protection